Knowledge attitude and practice (KAP) towards acceptance of human papillomavirus (HPV) vaccination among secondary school students in Kuching - Hamidi, Mohamad Sharkawi (Universiti Malaysia Sarawak, (UNIMAS), 2013)
A new vaccine, the HPV vaccine has been given for free via the school health program since the year 2011 with the aim of preventing the spread of HPV infection and reducing the incidence of cervical cancer. A study was conducted to determine the level of knowledge, attitude and practice towards HPV vaccination acceptance among secondary school students in Kuching. A cross-sectional study was conducted at five randomised selected public schools in Kuching City. A total of 387 students aged 13 to 14 years were recruited into the study.